Bacterial biomarkers - Honisch, Christiane (Henry Stewart Talks, 2012)
Bacterial infections and biomarkers, Bacterial biomarkers in today's diagnostic laboratories, Identification, classification, purpose and groups of biomarkers, Resolution and epidemiological analysis, Genomic, proteomic and metabolic markers, Mass spectrometry, Antibiotic resistance, Application examples of bacterial biomarkers